Pensamiento sistémico Amazónico y sostenibilidad: una perspectiva desde la cosmovisión de los indios Tukano (2020)
The following research aims to make a study of the Tukano indigenous tribe and their worldview from a deep analysis from the four waves of systemic thinking. The above, with the purpose of proposing a new approach to systems thinking from their worldview within the framework of sustainability.